Contributions to species of Xylariales in China—4. Hypoxylon wujiangensis sp. nov. - Pi, Yin-Hui; Zhang, Xu; Liu, Li-Li; Long, Qing-De; Shen, Xiang-Chun; Kang, Ying-Qian; Hyde, Kevin D.; Boonmee, Saranyaphat; Kang, Ji-Chuan; Li, Qi-Rui (Phytotaxa, 2020)
A species of Hypoxylon, found on dead wood in China, differs from H. hypomiltum and H. samuelsii in having highly carbonaceous stromata, asci with a long stipe and wider ascospores. Based on morphology and molecular phylogeny, it is described as a new species, H. wujiangensis sp. nov. A detailed description and illustration are provided, along with molecular evidence for the new species.